1999
DOI: 10.1103/physrevb.59.5832
|View full text |Cite
|
Sign up to set email alerts
|

Electron-energy-loss spectroscopy of plasmon excitations in concentric-shell fullerenes

Abstract: We report evidence for surface plasmon excitations in concentric-shell fullerenes. A film of these concentricshell fullerenes with radii around 5-7 nm was produced by carbon bombardment of a silver polycrystalline target and measured by electron-energy-loss spectroscopy ͑EELS͒ in reflection geometry. These data were analyzed with the help of a dielectric theory developed for EELS in transmission geometry. Taking into account the concentric-shell-substrate interaction, the spectral shape can be explained as a c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
26
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 29 publications
4
26
0
Order By: Relevance
“…11 However, the strong interaction with the silver substrate complicated the unambiguous identification of the surface and volume plasmons in the highly surface sensitive high-resolution EELS experiments. In the transmission EELS measurements presented here, the total absence of silver in the samples, combined with the negligible surface scattering contribution to the measured loss function, even at low q, 23 means that one arrives at the true, representative volume dielectric properties of concentric-shell fullerenes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…11 However, the strong interaction with the silver substrate complicated the unambiguous identification of the surface and volume plasmons in the highly surface sensitive high-resolution EELS experiments. In the transmission EELS measurements presented here, the total absence of silver in the samples, combined with the negligible surface scattering contribution to the measured loss function, even at low q, 23 means that one arrives at the true, representative volume dielectric properties of concentric-shell fullerenes.…”
Section: Resultsmentioning
confidence: 99%
“…8 The electronic properties of such carbon onions were characterized by spatially resolved electron energy-loss spectroscopy ͑EELS͒ in transmission 5,9,10 and by EELS in reflection. 11 From a comparison of the plasmon positions in transmission EELS and in reflection EELS at different geometries and electron beam energies, additional features were observed in the loss function, and were explained by tangential and radial surface plasmons. In addition simulations using a generalized model based on nonrelativistic local dielectric response theory were used to simulate spatially resolved EELS measurements of individual shells.…”
Section: Introductionmentioning
confidence: 99%
“…20 Furthermore, perfectly spherical shells were used in the theoretical modeling of the EELS data and the agreement was good. The model of Lucas, et al 23 was shown to be qualitatively adequate for understanding the optical data for multi-shell fullerenes.…”
Section: -10mentioning
confidence: 97%
“…Until now, the electronic properties of the onions were characterized only by spatially resolved EELS in transmission 15,18 and reflection mode. 19 Recently Sano et al [20][21][22] reported the production of several milligrams of carbon onions with diameters ranging from 4 to 36 nm using an arc discharge between two graphite electrodes submerged in water or liquid nitrogen. It has been shown that depending upon synthesis conditions the carbon nanoparticles produced by this method contain carbon onions with a perfect spherical shape along with defective carbon onions and a minimum amount of amorphous carbon and carbon nanotubes.…”
Section: Introductionmentioning
confidence: 99%